The Global Multidimensional Poverty Index 2024: harmonised level estimates and their changes over time - Alkire, S; Kanagaratnam, U; Suppa, N (OPHI, University of Oxford, 2024)
This Database provides estimates of the global Multidimensional Poverty Index (MPI) an international measure of acute poverty. More specifically, it contains harmonised level estimates and their changes over time of the global MPI and related sub-indices, which have been estimated for the 2024 release. For this Database all deprivation indicators have been harmonised over time.